Failures of once‐a‐week trimethoprim‐sulfamethoxazole prophylaxis in children undergoing allogeneic hematopoietic stem cell transplant. Issue 1 (27th December 2019) - Castagnola, Elio; Mesini, Alessio; Saffioti, Carolina; Moscatelli, Andrea; Pierri, Filomena; Giardino, Stefano; Faraci, Maura
Abstract: Once‐a‐week cotrimoxazole is an effective prophylaxis for pneumocystosis during antineoplastic chemotherapy or autologous stem cell transplant. Following allogeneic stem cell transplant, this schedule is at risk of pneumocystosis or neurotoxoplasmosis, as demonstrated by these case reports. Therefore, a 3‐times‐a‐week schedule must be adopted in these patients.